2018
DOI: 10.1097/prs.0000000000004380
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Conflict-of-Interest Disclosures Reported by Plastic Surgeons and Industry

Abstract: Discordance exists between investigator/authors self-reporting in scientific journals and the government-mandated reporting of conflicts of interest by industry. Factors associated with conflict-of-interest disclosure include academic status, transaction amount, and article content related to the sponsoring biomedical company.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Our finding that many guidelines either did not report or accurately report funding sources for the sponsoring organization and conflicts of interest for individuals is consistent with other studies and media reports [53,[76][77][78][79][80]. A recent ProPublica and New York Times investigation found that a top cancer researcher consistently failed to disclose millions in payments [81].…”
Section: Discussionsupporting
confidence: 84%
“…Our finding that many guidelines either did not report or accurately report funding sources for the sponsoring organization and conflicts of interest for individuals is consistent with other studies and media reports [53,[76][77][78][79][80]. A recent ProPublica and New York Times investigation found that a top cancer researcher consistently failed to disclose millions in payments [81].…”
Section: Discussionsupporting
confidence: 84%
“…Six studies reported on the association of the value of payments that were not disclosed. 11 13 14 28 35 37 Five found that authors who received smaller total payments or individual payments of lesser value were associated with discrepant reporting 11 13 14 28 37 Studies differed in what was reported to be considered 'significant' amounts, from US$500, 14 US$10 000, 11 28 US$100 000 11 13 to US$500 000. 37 The sixth study was the only one to report no statistically significant association between discrepant reporting and the value of the payments involved.…”
Section: Proportion Of Funds Discrepantmentioning
confidence: 99%
“…18 A recent study in plastic surgery found much discordance between COI self-reported by authors and that which was recorded in the "Open Payments" database. 12 It is apparent from our study, as well as the literature, that self-reporting of financial COI without validation is insufficient to ensure transparency of potential biases. Furthermore, and even more worrying, is the fact that past ethical studies have depended on the accuracy of self-reporting and have possibly underappreciated the incidence and prevalence of true COI based on the results demonstrated here.…”
Section: Discussionmentioning
confidence: 84%